Lanskap Linguistik Kawasan Istana Sisingamangaraja Di Kabupaten Humbang Hasundutan - Simamora, Mei Lisriani; Sibarani, Robert; Sinulingga, Jekmen; Sinaga, Warisman; Damanik, Ramlan (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2025)
This study analyzes the linguistic landscape of the Sisingamangaraja Palace area in Humbang Hasundutan Regency as a representation of cultural identity, language ideology, and strategies for preserving cultural heritage in public space. The study is grounded in Landry and Bourhis’s linguistic landscape theory and Stuart Hall’s perspective of cultural representation. A descriptive qualitative method was employed through visual observation, photographic documentation, and interviews with key informants. Data were interpretively analyzed to examine the use of Indonesian, Batak Toba language, English, and Batak script across various visual media. The findings indicate that the linguistic landscape functions not only informationally but also symbolically, representing historical legitimacy, cultural authority, and spirituality, while serving as a site of negotiation between locality, nationality, and globality in strengthening the collective memory of the Batak community.